Energy performance heterogeneity in China's buildings sector: A data-driven investigation - Li, Jun (2016)
© 2016 Elsevier Ltd. All rights reserved. The significant variation in building's energy intensity is partly due to the large number of distributed energy users characterized by heterogeneous lifestyles and nonuniform consumption behaviours. Understanding the degree of variation and its cause is critical to designing appropriate policies for energy efficiency improvement. This paper aims to provide a data-based benchmark of buildings energy performance in China and investigates the facts and causes of large variations in energy consumption across buildings based on updated and harmonised dataset. Specifically, the paper is the first in literature to decompose aggregate heating consumption in northern urban China and reallocate the disaggregate data to relevant residential and commercial building energy use, which makes it consistent to conduct international comparison of building performance in terms of primary energy intensity. It is found that buildings energy performance exhibits a sizeable heterogeneity varying with building typology and climate zones in China. Heating and cooling energy consumption for residential buildings located in HSCW climate zone may differ by a factor of 4-10 depending on the technology and energy supply mode, whereby nontechnical interventions may have significant impacts on total energy demand in the built environment. In particular, our analysis results point to the importance of making greater efforts in the commercial sector. Commercial buildings are found significantly more energy intensive than their residential counterpart, mainly due to the fact that BEE policy has been poorly implemented and architectural design has not been optimised in commercial sector. An estimate suggests that improving energy efficiency in the commercial sector may contribute to one-fifth of total energy savings potentials by 2020 in line with the IEA's 450 ppm scenario. It is necessary for Chinese building authorities to incorporate the heterogeneity characteristics across different climate zones and building typologies into BEE policy portfolio to effectively curb energy consumption related carbon emissions.